2017
DOI: 10.1111/jgs.14884
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey on the Effect of the Geriatric Academic Career Award in Advancing Academic Geriatric Medicine

Abstract: A workforce that understands principles of geriatric medicine is critical to addressing the care needs of the growing elderly population. This will be impossible without a substantial increase in academicians engaged in education and aging research. Limited support of early‐career clinician–educators is a major barrier to attaining this goal. The Geriatric Academic Career Award (GACA) was a vital resource that benefitted 222 junior faculty members. GACA availability was interrupted in 2006, followed by permane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…A recently published analysis demonstrated that each GACA recipient had an impact on approximately 183 interdisciplinary trainees. 23 Based on these data, we project that 9,300 additional health professionals would receive palliative care education and training through palliative care academic career development awards.…”
Section: Policy Implications and Opportunitiesmentioning
confidence: 99%
“…A recently published analysis demonstrated that each GACA recipient had an impact on approximately 183 interdisciplinary trainees. 23 Based on these data, we project that 9,300 additional health professionals would receive palliative care education and training through palliative care academic career development awards.…”
Section: Policy Implications and Opportunitiesmentioning
confidence: 99%
“…Consequently, geriatrics healthcare professionals from multiple disciplines are uniquely positioned to lead a new effort to develop and implement geriatrics‐focused training and mentorship (see Table ). Innovative models of interprofessional geriatric care would ideally be catalyzed by renewed support for the Health Resources and Services Administration (HRSA) Geriatric Academic Career Award and the Geriatric Wokrforce Enhancement Program (GWEP) . In particular, there is an urgent need to develop geriatrics‐focused interprofessional training and mentorship activities for junior clinician‐educator faculty members in the areas of aging (including healthy aging), dementia, and mental health.…”
Section: Interprofessional Team Training and Competency In Geriatricsmentioning
confidence: 99%
“…Summit attendees lauded this program for providing grantees opportunities to develop innovative approaches to provide geriatrics education throughout a region, often including staff and clinicians in primary care, adult day care health centers, and other sites. Summit attendees also pointed to the Geriatrics Academic Career Award program that was interrupted in 2005 but reestablished shortly after the summit . Summit attendees recommended that a program be established to support palliative care using the successful model of the GWEPs.…”
Section: Recommendationsmentioning
confidence: 99%